2013
DOI: 10.1186/1742-2094-10-91
|View full text |Cite|
|
Sign up to set email alerts
|

A new co-ultramicronized composite including palmitoylethanolamide and luteolin to prevent neuroinflammation in spinal cord injury

Abstract: BackgroundIt has recently been demonstrated that palmitoylethanolamide (PEA), an endogenous lipid amide belonging to the N-acylethanolamine family, exerts neuroprotection in central nervous system (CNS) pathologies. In recent studies, we have demonstrated that treatment with PEA significantly reduced inflammatory secondary events associated with spinal cord injury (SCI). Since oxidative stress is considered to play an important role in neuroinflammatory disorders, in the present work we studied a new composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 25 publications
5
78
0
Order By: Relevance
“…NO is a unique molecule involved in a variety of physiological processes in the CNS [65]. The effects of NO on spinal cord damage are correlated with several factors, such as concentration of NO production, activity of different synthase isoforms, cellular source of production, and time of release [35]. In this study, we demonstrated increased NO expression after injury, reduced by 18B12 pretreatment.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…NO is a unique molecule involved in a variety of physiological processes in the CNS [65]. The effects of NO on spinal cord damage are correlated with several factors, such as concentration of NO production, activity of different synthase isoforms, cellular source of production, and time of release [35]. In this study, we demonstrated increased NO expression after injury, reduced by 18B12 pretreatment.…”
Section: Discussionsupporting
confidence: 52%
“…Total nitrite levels, as an indicator of nitric oxide (NO) synthesis, were measured in the supernatant as previously described [35].…”
Section: Measurement Of Nitrite Levelsmentioning
confidence: 99%
“…Our study included patients with different causes and levels of SCI, which could impact the outcome, and patients with concomitant medication which could have an impact on the effect of PEA-um, and it is likely that we included some patients that are refractory to pain treatment, which could also contribute to the lack of effect, also considering that more patients randomized to PEA were treated with concomitant medication. Finally it is possible, that the effect seen in experimental studies is driven mainly by reduced inflammation and neuroprotective mechanisms [13,29] and that treating spinal cord-injured individuals with PEA-um in early stages and before neuropathic pain and spasticity develop, may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PEAluteolin combination can reduce inflammatory processes associated with spinal cord injury and TBI by restoring basal expressions of peroxisome proliferator-activated receptors (PPARs) and by limiting nuclear factor-kB (NF-kB) activation Paterniti et al, 2013). Moreover, PEA-luteolin association Fig.…”
Section: Discussionmentioning
confidence: 99%